INTERACTIVE COMMUNICATION WITH EDMODO IN EFL CLASSROOM - Yuliana Ningsih; Wan Yuliyanti (English Study Program University of Pasir Pengaraian, 2021)
Virtual learning is very much important in the 21st century in increasing interest in communicating in EFL classrooms. Edmodo is one of the media used for virtual learning. This research primarily aimed at describing interactive communication and students’ perspective of the online media